The power of sight : the impact of AR Smart Glasses on the smartphone industry - Santos, Beatriz Marina Costa dos (2022)
The smartphone industry has experienced a phenomenal growth in the last 15 years of its existence, but it has begun to plateau. This dissertation evaluates the likelihood of an emerging Smart Wearable (SW), the AR Smart Glasses, significantly impacting the smartphone industry. This research used qualitative and quantitative methods, including 14 expert interviews, to better understand the workings of AR and future potential of AR Smart Glasses, as well as a survey with 196 respondents to determine what consumers think about AR Smart Glasses. Experts believe that AR Smart Glasses will have a significant impact on the smartphone industry, and even take its place in the future, but there is a lack of confidence regarding the time period in which may occur. Experts believe the biggest threats to its success are its affordability, AR's complex technology, and the lack of consumer education on the issue. The success of AR Smart Glasses was viewed with skepticism by respondents. They are more interested in its capacity to improve engagement with reality than in having another platform to consume content, and were primarily worried about how it would affect their comfort and interfere with reality. They prefer to check time, notifications, weather, use GPS, voice assistant and take pictures on AR Smart Glasses, but given that the majority of respondents consider themselves unfamiliar with AR and AR Smart Glasses, their preferences may shift to AR Smart Glasses once they gain a better understanding of the device's potential.